Efficient Allocation of Land between Productive Use and Recreational Use - An Application to Galician Case - Eduardo L. Giménez; Manuel González-Gómez (Tinbergen Institute, 2001)
In this paper the efficient allocation of natural recreational areasis analysed. Natural recreational areas have the features of publicgoods. We present the efficient allocation of this non-excludablepublic good in a rational general equilibrium model withheterogeneous agents. This allows us to deal with the free-riderproblem in the provision of the public good. This framework could beconsidered as a microfoundation of the Lopez, Shah and Altobello(1994) model. In addition we study both the existence value and theuse value of the recreational area in the same setting. Amethodological critique is also made of previous empiricalliterature. It is suggested that our theoretical framework is asuitable starting point for further empirical research. Finally anempirical application for the Galician case is presented. Our resultssuggest that current allocations of land to natural recreationalareas in Galiza are not efficient.
Keywords: Q21; Q24; Q26; D51; D10; 330; Land Allocation; Efficient Allocation; Natural Recreational Areas; Public Good; Social Planner Problem; Voluntary Contribution Competitive Equilibrium; Use Value; Existence Value; Tourismusregion; Bodennutzung; Allokationseffizienz; Öffentliche Güter; Pareto-Optimum; Schätzung; Theorie; Galicien (Spanien)